Enhancing superconducting properties and grain connectivity of magnesium diboride via dopant additions - Mohd Hapipi, Nurhidayah (2022)
In this work, both ex-situ and in-situ methods were used to synthesise MgB2 samples. Pure ex-situ MgB2 sample (Series 1) was sintered at various temperatures (600-900 °C) and times (1-7 h). Several dopants such as excess Mg (Series 2), (1.5 Mg + 2 B) (Series 3), nano-Si (Series 4), nano-Si + LaB6 (Series 5), and Dy2O3 + La2O3 (Series 6) were added into MgB2. For series 1, increasing the sintering temperature to 900 °C increased the Jc value (0 T, 20 K) to 4.2 × 103 A/cm2, suggesting an enhancement in sample grain coupling. A prolonged sintering time of 3 h increased the Jc value to 3.2 × 103 A/cm2 before decreasing to 0.5 × 103 A/cm2 when the sintering time was prolonged to 7 h. Meanwhile, the addition of excess Mg into ex-situ MgB2 (Series 2) successfully inhibits MgB2 decomposition where no MgB4 peaks were observed in the Mg-added sample, in contrast to pure ex-situ MgB2 which exhibited MgB4 peaks at higher sintering temperatures. When the sintering temperature increased, the addition of excess Mg reduced the average grain sizes and further strengthened the grain coupling of the samples, which subsequently increased the Jc value to 104 A/cm2, which is more than 20 times. In Series 3, the addition of 0 to 50 wt.% of (1.5 Mg + 2 B) increased the Jc (0 T, 20 K) value from 3.0 × 103 A/cm2 to 1.3 × 104 A/cm2, respectively. The highest Jc (0 T, 20 K) value obtained for Series 3 was 2.1 × 104 A/cm2 for the sample sintered at 1000 C. XRD pattern for nano-Si added into in-situ MgB2 samples (Series 4) shows the formation of Mg2Si where excess Mg2Si can obstruct the current pathway of the samples and lower the value of Jc. The addition of nano-Si from 0 to 10 wt.% decreased the value of Jc (0 T, 20 K) from 2.4 × 105 A/cm2 to 1.7 × 105 A/cm2, respectively. However, the Jc value at high field increased to 2.8 × 103 A/cm2 with the addition of 5 wt.% of nano-Si. The co-addition of 0.03 mol LaB6 and x wt.% nano-Si (Series 5) inhibited the grain growth of the samples as no significant changes in average grain size were observed. The addition of LaB6 decreased Jc (0 T, 20 K) to 2.12 × 105 A/cm2, and it further decreased to 1.7 × 105 A/cm2 with co-addition of LaB6 and 10 wt.% of nano-Si. Co-addition of Dy2O3 and La2O3 into MgB2 (Series 6) enhanced the flux pinning of the samples and the Jc value, where the highest Jc (0 T, 20 K) value obtained was 4.3 × 105 A/cm2 for 1.00 wt.% co-added samples.